Molecular mechanism of anesthetic‐induced depression of myocardial contraction. Issue 8 (11th May 2016) - Meng, Tao; Bu, Weiming; Ren, Xianfeng; Chen, Xinzhong; Yu, Jingui; Eckenhoff, Roderic G.; Gao, Wei Dong
ABSTRACT: Isoflurane and propofol are known to depress cardiac contraction, but the molecular mechanisms involved are not known. In this study, we determined whether decreasing myofilament Ca 2+ responsiveness underlies anesthesia‐induced depression of contraction and uncovered the molecular targets of isoflurane and propofol. Force and intracellular Ca 2+ ([Ca 2+ ]i ) were measured in rat trabeculae superfused with Krebs‐Henseleit solution, with or without propofol or isoflurane. Photoaffinity labeling of myofilament proteins with meta‐Azi‐propofol (AziP m ) and Azi‐isoflurane (Azi‐iso) and molecular docking were also used. Both propofol and isoflurane dose dependently depressed force from low doses (propofol, 27 ± 6 μM; isoflurane, 1.0 ± 0.1%) to moderate doses (propofol, 87 ± 4 μM; isoflurane, 3.0 ± 0.25%), without significant alteration [Ca 2 +]i . During steady‐state activations in both intact and skinned preparations, propofol and isoflurane depressed maximum Ca 2+ ‐activated force and increased the [Ca 2+ ]i required for 50% of activation. Myofibrils photolabeled with AziP m and Azi‐iso identified myosin, actin, and myosin light chain as targets of the anesthetics. Several adducted residues in those proteins were located in con‐formationally sensitive regions that underlie contractile function. Thus, propofol and isoflurane decrease force development by directly depressing myofilament Ca 2+ responsiveness and have binding sites in key regions for contraction in both actin and myosin.—Meng, T., Bu, W., Ren, X., Chen, X., Yu, J., Eckenhoff, R. G., Gao, W. D. Molecular mechanism of anesthetic‐induced depression of myocardial contraction. FASEB J. 30, 2915‐2925 (2016). www.fasebj.org